Projectability as a Criterion for Income Determination Methods. - Louderback, III, Joseph G. (The Accounting Review, 1971)
Abstract The article analyzes the rationale of arguments that projectability should be a criterion for acceptance of income determination schemes on grounds that income prediction is relevant to investor decisions. The value formulations generally accept a neo-classical theory of value, and therefore income, in which "value" is the present value of, expected future cash flows. Income is the difference between these values at points in time excluding capital transactions and adding back dividend payments. Under this notion, income is an ideal, an immutable concept. Advocates of the development of meanings and operations for income determination, which are projectable, may contend that income prediction is well recognized as a tool of security analysis. The conditions under which any accounting income amount is functionally related to such events as future cash flows are largely unspecified. Therefore, the functional status of projectable income meanings and operations is indeterminate and independent of considerations of relevance.